Use of landscape environmental setting for pedestrian to enhance campus walkability and healthy lifestyle - Kasim, Zanariah; Shahidan, Mohd Fairuz; Yusof, Yusma (WIT Press, 2018)
Malaysian higher learning institutions were designed to create environments conducive for teaching and learning. Campuses are often large ranging from a few hundred to more than a thousand hectares. These require a proper connecting system without undermining the value of a healthy lifestyle. Walking is an element that promotes healthy lifestyle. The aim of this research is to enhance campus walkability within different landscape environmental settings in tropical campus environments. The study investigated and measure Landscape Environmental Setting for Pedestrian (LESP) based principally on physical properties of the landscape setting and its surrounding environment. This study will highlight the tropical campus environment by using pedestrian walkways, with different settings, as a case study. To achieve the objectives, the study used literature review and a case study. The literature reviews and observations help to identify and classify landscape scenarios of various landscape settings. The campuses involved in this study are Universiti Kebangsaan Malaysia (UKM), Universiti Putra Malaysia (UPM), Universiti Malaya (UM) and Politeknik Port Dickson (PPD). All four institutions were used as a case study to evaluate the existing condition of the pedestrian environment. The key constructs used in the literature review are pedestrian thermal comfort and landscape environment setting. Case study method was used to evaluate the relationship between LESP, pedestrian thermal comfort, and various settings of campus landscape scenarios. The results of the study revealed that different types of LESP have potential in providing a better campus environment and lifestyles. Importantly, the landscape design attributes and characteristics play an important role in the development of a design guideline in the context of sustainable tropical campus environment perspective.